2021
DOI: 10.3390/pr9030431
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Absent Air Column in Three Products Hydrocyclone Screen (TPHS): Experiment and Simulation

Abstract: Three products hyrdrocyclone screen (TPHS) has been proposed for particle separation based on size. In TPHS, a cylindrical screen was embedded in a conventional hydrocyclone (CH) to combine the centrifugal classification and screening to particle separation based on size. The industrial application of TPHS indicates its better device performance than CH. Although, the earlier studies reveal some common understanding for TPHS, the information of the absent air column remains unknown. Hence, the combination of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Our earlier work exhibits that TPHS has a higher radial velocity and a lower tangential velocity than CH, which can help fine particles to pass through the screen [14]. The following study revealed that due to the unformed negative pressure zone near outlets, the absent air column in TPHS can be observed to reduce the energy consumption [16]. The prior studies reveal some common comprehensions for TPHS; however, the details of flow characteristics including the pressure distribution and turbulent features remain unknown.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Our earlier work exhibits that TPHS has a higher radial velocity and a lower tangential velocity than CH, which can help fine particles to pass through the screen [14]. The following study revealed that due to the unformed negative pressure zone near outlets, the absent air column in TPHS can be observed to reduce the energy consumption [16]. The prior studies reveal some common comprehensions for TPHS; however, the details of flow characteristics including the pressure distribution and turbulent features remain unknown.…”
Section: Introductionmentioning
confidence: 80%
“…In addition, the fluid behavior near the wall region was modeled using the stand wall function, shown as follows [16]:…”
Section: Numerical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the size of the WNT assembly in CFD simulation is consistent with that in the experiment (Figure ). The combination of the VOF and the RSM , was used to describe the fluid flow in the WNT. The VOF model serves to characterize the liquid–gas two-phase fluid using water and air in the WNT, as shown in eqs –. 1 ρ normalq [ ∂t false( α normalq ρ normalq false) + · false( α normalq ρ normalq u normalq false) ] = prefix∑ normalp = 1 n ( m pq m qp ) normalq = 1 n α normalq = 1 t ( ρ v⃗ ) + · ( ρ v⃗ v⃗ ) = prefix− p + μ ( v⃗ …”
Section: Methodsmentioning
confidence: 99%